2018
DOI: 10.3390/ijms19020593
|View full text |Cite
|
Sign up to set email alerts
|

Luminal lncRNAs Regulation by ERα-Controlled Enhancers in a Ligand-Independent Manner in Breast Cancer Cells

Abstract: Estrogen receptor-α (ERα) is a ligand-inducible protein which mediates estrogenic hormones signaling and defines the luminal BC phenotype. Recently, we demonstrated that even in absence of ligands ERα (apoERα) binds chromatin sites where it regulates transcription of several protein-coding and lncRNA genes. Noteworthy, apoERα-regulated lncRNAs marginally overlap estrogen-induced transcripts, thus representing a new signature of luminal BC genes. By the analysis of H3K27ac enrichment in hormone-deprived MCF-7 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 59 publications
3
18
0
Order By: Relevance
“…We previously demonstrated that DSCAM-AS1 is an ERα-regulated lncRNA [ 9 , 13 ]. We thus compared the list of DE genes obtained in this study with those DE upon ERα silencing [ 13 ]. Notably, 526 genes were detected as DE in both datasets (hypergeometric test p < 4.36 × 10 −48 , representation factor = 1.7) ( Figure 2 e and Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously demonstrated that DSCAM-AS1 is an ERα-regulated lncRNA [ 9 , 13 ]. We thus compared the list of DE genes obtained in this study with those DE upon ERα silencing [ 13 ]. Notably, 526 genes were detected as DE in both datasets (hypergeometric test p < 4.36 × 10 −48 , representation factor = 1.7) ( Figure 2 e and Table S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that DSCAM-AS1 was also detected as highly expressed in HER2-amplified, ER-negative tumors, suggesting an ERα-independent mechanism enhancing its expression in this BC subtype. As previously shown by our group, a super-enhancer region is localized upstream of the DSCAM-AS1 locus and it is involved in the regulation of this lncRNA [ 13 ]. This genomic region can represent a platform for the recruitment of different transcriptional regulators, including the Transcription Factor AP2-γ (AP2-γ), which was previously reported to lead overexpression of the ERBB2 gene [ 32 ] and, in complex with other transcription factors, it could drive the DSCAM-AS1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations